Elaborasi Modul Ajar Pendidikan Agama Islam Berbasis Kurikulum Merdeka di SMP Negeri 5 Kota Serang Banten - Cahyawati, Ita; Wawan Wahyuddin; Subhan Subhan; Wasehudin Wasehudin; Fandi Adpen Lazzavietamsi (STAI Terpadu Yogyakarta, 2024)
The study aims to investigate the phenomena being examined through a comprehensive analysis of relevant literature and to examine instructional modules that are in line with the independent learning curriculum. The teaching module serves as an autonomous curriculum framework that can be used as an alternative to the traditional lesson plan. It covers a wide range of learning materials, instructional approaches, interpretations, and evaluation methods that are systematically arranged with the aim of achieving desired indicators of success. Educators formulate pedagogical modules before applying instruction in classroom settings. One of the main purposes of the teaching module is to ease the workload of educators in delivering teaching materials, thus giving them extra time to engage in personalized instruction and support students throughout their learning journey.